Community Empowerment Through Village-Owned Enterprises in Bintang Ara Village, Gunung Bintang Awai District - Singgih Priono; Risal, Semuel; Moh. Heru Budihantho; Irma Yanti (PT FORMOSA CENDEKIA GLOBAL, 2024)
Community empowerment is an important effort to improve the welfare and development of a village. Bintang Ara Village, located in Gunung Bintang Awai District, has taken progressive steps by developing Village-Owned Enterprises (BUMDes) as a tool to achieve sustainable community empowerment. This process involves several key stages that have proven effective in driving the development of this village. The first stage is the awareness stage. At the start of the journey, the people of Bintang Ara Village were invited to understand the importance of BUMDes as an instrument to drive their empowerment. Through dialogue and outreach, village residents are starting to realize the potential of local resources that can be utilized through BUMDes. The next stage is training. To ensure the success of BUMDes, village residents are given training in various aspects, such as business management, finance, marketing and relevant technical skills. This allows them to become more competent in managing BUMDes well. Mentoring is the next stage in the empowerment process. The accompanying team works together with BUMDes to help them overcome obstacles and challenges that may arise during their operations. This assistance includes monitoring progress, providing guidance, and providing practical solutions to problems that arise. Last, but not least, is the evaluation stage. The local government and community regularly evaluate the performance of BUMDes and its impact on village welfare. The evaluation results are used to design steps for further improvement and development so that BUMDes remain effective in empowering the community